Development of Health Literacy Program in Promoting the Use of Blue Book Application Among the Elderly in Thung Hua Subdistrict, Wang Nuea District, Lampang Province - Tachan , Nattapong; Tiamjan , Rapeeporn; Deethae , Aomhatai (Journal of Nursing, Siam University, 2024)
This research is a study and development The objectives were 1) to study the situation and health literacy on blue book application using among the elderly 2) to develop a health literacy program in promoting the use of blue book application, and 3) to evaluate the effectiveness of the program. The sample group in this study was the elderly who live in Thung Hua Subdistrict, Wang Nuea District, Lampang Province, and simple random sampling was used. The research tools consisted of general information questionnaires and health literacy questionnaires on the use of blue book application. Data was analyzed by using descriptive statistics and compared the mean values ​​with Paired Sample t-test. The results of the study found that most of the 322 elderly people did not know about the blue book application and accessed information about the application from public health personnel. The overall health literacy in using the application of the elderly people was insufficient ( = 54.67, SD = 8.11). The developed program consisted of: Section 1: Memory (Mini-cog), Section 2: Physical Movement (Timed Up and Go test: TUGT), Section 3: Malnutrition, Section 4: Vision, Section 5: Hearing, Section 6: Depression, Section 7: Urinary retention, Section 8: Daily routines, and Section 9: Oral health. The evaluation of the effectiveness of the health literacy program in promoting the use of the of blue book application among 44 elderly people found that after participating in the program, The elderly had higher health literacy scores ( = 97.47, SD = 3.60) than before joining the program ( = 49.09, SD = 7.06) and the difference was statistically significant (t = -47.294, p < 0.001).